Operationalizing growth models - Lucio Baccaro; Sinisa Hadziabdic (Max Planck Institute for the Study of Societies, 2022)
We present a new methodology for operationalizing growth models based on import-adjusted demand components. Applying the methodology to the latest release of OECD Input-Output Tables, we calculate the growth contributions of consumption, investment, government expenditures, and exports for sixty-six countries in the periods 1995 to 2007 and 2009 to 2018 and identify the respective growth models. We find that most countries are export-led or domestic demand-led and that other forms of growth are rare. Our results corroborate previous classifications in comparative political economy but also differ from them in significant respects. Importantly, our classification improves on previous ones by covering not just the advanced capitalist economies but also Central and Eastern European and South-East Asian and Latin American countries. In a further step, we illustrate how the new indicators can be used to analyze the "drivers" of different types of growth. This examination reveals that there is a clear trade-off between consumption- and export-led growth in advanced Western economies in the period 1995 to 2007 and a dependence of export-led growth in these countries on real exchange rate devaluation in the same period, while export complexity is not a significant predictor of export-led growth. – – Wir stellen eine neue Methode zur Operationalisierung von Wachstumsmodellen auf der Grundlage importbereinigter Nachfragekomponenten vor. Dabei berechnen wir anhand der aktuellen Input-Output-Tabellen der OECD den jeweiligen Wachstumsbeitrag von Konsum, Investitionen, Staatsausgaben und Exporten für 66 Länder in den Zeiträumen 1995-2007 und 2009-2018 und ermitteln die entsprechenden Wachstumsmodelle. Es zeigt sich, dass die meisten Länder ein vom Export oder von der Inlandsnachfrage getragenes Wachstum aufweisen und andere Wachstumsformen selten sind. Unsere Ergebnisse bestä- tigen bisherige Klassifikationen der Vergleichenden Politischen Ökonomie und unterschei- den sich gleichzeitig in wesentlichen Punkten von ihnen. Vor allem hat unsere Klassifikati- on im Vergleich zu bisherigen den Vorteil, dass sie sich nicht nur auf die fortgeschrittenen kapitalistischen Wirtschaftsordnungen, sondern auch auf Länder in Mittel- und Osteuropa und in Südostasien und Lateinamerika bezieht. Darüber hinaus erläutern wir, wie die neuen Indikatoren genutzt werden können, um die "Treiber" verschiedener Wachstumsformen zu ermitteln. Unsere Auswertung der Daten legt offen, dass es in fortgeschrittenen westli- chen Volkswirtschaften im Zeitraum 1995-2007 klare Zielkonflikte zwischen konsum- und exportorientiertem Wachstum und eine Abhängigkeit des exportorientierten Wachstums von realen Wechselkursabwertungen gegeben hat, während die Komplexität der Exporte keinen wesentlichen Einfluss auf das exportorientierte Wachstum hatte.
hdl:21.11116/0000-000B-53B7-9
Keywords: 300; advanced economies; emerging economies; export-led growth; growth models; input-output tables; political economy; entwickelte Volkswirtschaften; exportorientiertes Wachstum; Input-Output-Tabellen; politische Ökonomie; Schwellenländer; Wachstumsmodelle